2014
DOI: 10.1039/c4ra03988b
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in electrical and electrochemical properties of Nb-doped SnO2−δ supports for fuel cell cathodes due to aggregation and Pt loading

Abstract: We found the specific activities of Pt/Sn0.96Nb0.04O2−δ for the oxygen reduction reaction increased with increasing conductivity of the support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
104
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(113 citation statements)
references
References 40 publications
(46 reference statements)
9
104
0
Order By: Relevance
“…The value of jk of Pt/TiC-600 °C at 0.85 V was 0.70 mA cm −2 , which was approximately 1.4 times higher than that of cPt/CB. Similar enhancement factors of the jk were also reported for Pt/Nb-SnO2−δ and Pt/Ta-SnO2−δ [29,30]. The value of MA of Pt/TiC-600 °C at 0.85 V (507 A g ), since the ECA of Pt/TiC-600 °C was smaller than that of c-Pt/CB.…”
Section: Electrochemical Characterization Of Pt/tic Catalystssupporting
confidence: 79%
See 3 more Smart Citations
“…The value of jk of Pt/TiC-600 °C at 0.85 V was 0.70 mA cm −2 , which was approximately 1.4 times higher than that of cPt/CB. Similar enhancement factors of the jk were also reported for Pt/Nb-SnO2−δ and Pt/Ta-SnO2−δ [29,30]. The value of MA of Pt/TiC-600 °C at 0.85 V (507 A g ), since the ECA of Pt/TiC-600 °C was smaller than that of c-Pt/CB.…”
Section: Electrochemical Characterization Of Pt/tic Catalystssupporting
confidence: 79%
“…By TEM observation, we have clearly demonstrated that the major reason for such a high durability of Pt/TiC-600 °C was suppression of the detachment of Pt particles from the support, unlike c-Pt/CB. Hence, based on our systematic work using various ceramic supports (TiN [26], doped SnO2 [27][28][29][30], and TiC in the present work), the essential factors for the highly active and highly durable cathode catalysts are the use of a chemically and electro chemically stable support with high electrical conductivity, uniform dispersion of Pt nanocrystals on the support, and the removal of an oxide layer, if any, on the Pt surface and/or Pt-ceramic support interface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[30][31][32][33] Briefly, reagent grade 2-ethylhexanoate salts of Sn and Ta (Nihon Kagaku Sangyo, Co. Ltd.) were mixed at desired ratios into turpentine oil. The mixtures were supplied into the burner (>1000…”
Section: Methodsmentioning
confidence: 99%